Pengaruh Motivasi Belajar terhadap Hasil Belajar Siswa pada Tema 1 Subtema 2 Manusia dan Lingkungan di Kelas V SD Percontohan 091317 Pematang Raya - Inde Crysanta; Lisbet N. Sihombing; Eva Pasaribu (Medan Resource Center, 2022)
This study focuses onHumankind and the Environment sub-theme 2 Thematic learners were motivated to learn thanks to this study. The goal of the study was to improve student learning outcomes. The study involves two variables: learner outcomes and motivation to learn. It involves 54 students as the research population, but a smaller sample of 30 students was used for data collection. Two methods were used to collect data: questionnaires and tests. Then, quasi-experimental methods were used to analyze the data. This means the researchers used hypothesis testing and normality testing. A data set was collected from 30 students regarding their learning outcomes. This included two subthemes and one main theme; the data set had a final score of 2335. The highest score was 95 and the lowest was 70. Additionally, a learning motivation questionnaire was given to 30 subjects. The data collected showed a total score of 2298— the average value was 77.826. The lowest score was 75 and the highest was 79. By performing a hypothesis test, it was determined that the Fcount and Ttable values were 10.041 and 3.169. Neither value crossed 0.05 or 0.04, meaning the results were significant but not significant enough to be considered significant. Consequently, it can be stated that there is a significant correlation between learner motivation and learning outcomes.